Distribusi Kekayaan dalam Ekonomi Islam : Analisis Zakat, Infak, dan Wakaf sebagai Instrumen Pemerataan - Nadya Nadya; Nabila Sekar Sari; Sabrina Dewi Hasna (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Inequality in wealth distribution is a serious problem in the modern economic system. The gap between high and low income groups continues to widen, triggering various social problems. In the perspective of Islamic economics, zakat, infaq and waqf are present as instruments that not only have worship values, but also significant social and economic functions. This study aims to analyze the contribution of these three instruments in reducing the inequality of wealth distribution in society. Through descriptive qualitative approach and literature study, this research examines various literatures and secondary data obtained from zakat, infaq, and waqf management institutions in Indonesia. The results show that zakat, infaq, and waqf are able to act as effective wealth redistribution tools, improve the welfare of vulnerable groups, and strengthen social cohesion. These three instruments are proven to be a systemic solution in creating a more equitable economic balance. Therefore, accountable, professional, and trustworthy management is needed so that the socio-economic potential of zakat, infaq, and waqf can be optimized in supporting the creation of social justice according to Islamic teachings.